Leviticus : a commentary on Leueitikon in Codex Vaticanus - Awabdy, Mark A., 1981- (Septuagint Commentary Series., 2019)
In Leviticus Awabdy offers the first commentary on the Greek version of Leviticus according to Codex Vaticanus (4th century CE), which binds the Old and New Testaments into a single volume as Christian scripture. Distinct from other LXX Leviticus commentaries that employ a critical edition and focus on translation technique, Greco-Roman context and reception, this study interprets a single Greek manuscript on its own terms in solidarity with its early Byzantine users unversed in Hebrew. With a formal-equivalence English translation of a new, uncorrected edition, Awabdy illuminates Leueitikon in B as an aesthetic composition that not only exhibits inherited Hebraic syntax and Koine lexical forms, but its own structure and theology, paragraph (outdented) divisions, syntax and pragmatics, intertextuality, solecisms and textual variants.